1986
DOI: 10.1136/bjsm.20.3.103
|View full text |Cite
|
Sign up to set email alerts
|

An holistic approach to recovery from an overuse injury in a games player.

Abstract: The management of a chronic injury to an international squash player is described. By good physiotherapeutic management and the involvement of an interdisciplinary team it was possible to make gains in the non-playing period. The rehabilitation period included physiological assessment on the basis of which a training programme was devised with target goals set throughout the period. Mental rehearsal of skills was included at all stages. As a result, the player's confidence was maintained and fitness levels imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…In total, 2544 participants are included in the review and 2264 completed treatments (post-treatment n) and were included in the meta-analytical calculations, 1227 in intervention groups and 1037 in control groups. Twenty-one studies assessed depressive symptoms,44–64 while MDD was diagnosed in 20 studies 65–84. Percentage of females ranged from 26% to 100%, mean age from 18.8 to 87.9 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 2544 participants are included in the review and 2264 completed treatments (post-treatment n) and were included in the meta-analytical calculations, 1227 in intervention groups and 1037 in control groups. Twenty-one studies assessed depressive symptoms,44–64 while MDD was diagnosed in 20 studies 65–84. Percentage of females ranged from 26% to 100%, mean age from 18.8 to 87.9 years.…”
Section: Resultsmentioning
confidence: 99%
“…Risk of bias assessment revealed 12 studies to be rated of low risk of bias,49 58 60 65 66 68–70 74 79 80 82 while 7 were rated with some concerns 44 45 48 51 55 73 76. For 22 studies, RoB2 indicated high risk for bias 46 47 50 52–54 56 57 59 61–64 67 71 72 75 77 78 81 83 84. For full details, see online supplemental table 3.…”
Section: Resultsmentioning
confidence: 99%
“…De forma general la tendencia de este enfoque se evidencia a través de los estudios de Nixon (1973), refiriéndose sobre el papel de los médicos en los equipos deportivos, o sea fue uno de los primeros que hablo sobre los equipos de apoyo al entrenador como una arista de la gestión deportiva. Nimmo, McLean, Mutrie & McKenzie (1986), establecen el enfoque holístico (gestión en la rehabilitación) para la recuperación de una lesión por uso excesivo en un jugador de juegos.…”
Section: Enfoque Gestión Deportivaunclassified